Development of anion-exchange membrane for anion-exchange membrane fuel cells. (June 2015) - Dong, X.W.; Zhuang, J.B.; Huang, N.B.; Liang, C.H.; Xu, L.S.; Li, W.; Zhang, S.C.; Sun, M.
Abstract : Anion-exchange membrane fuel cells possess several important advantages, and have attracted a lot of attention. In this paper, the characteristic of different type anion-exchange membrane were introduced. In view of the ion conductivity and stability of anion-exchange membrane, these anion-exchange membranes based on polybenzimidazole, polytetrafluoroethylen polysulfone, polyvinyl alcohol/poly(vinylpyrrolidone) blend membrane, poly(ethylene-co-vinyl benzyl chloride) (LDPE-co-VBC) will be the potential polymer electrolyte for anion-exchange membrane fuel cells.